(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
Competition is the driving force behind the development of society, the main tool for saving resources, improving the quality of goods and the standard of living of the population. The competitiveness of a product is a comprehensive characteristic of a product that determines its preference in the market compared to competing products both in terms of the degree of compliance with a specific social need and in terms of the costs of satisfying it. The competitiveness of products is measured by a set of indicators organized into four groups: qualitative, economic, organizational and commercial and socio-organizational indicators.